Portuguese women's activity in the past: comparing entheseal changes through time - Henderson, Charlotte (2018)
The aim of this paper is to study EC in females from the mediaeval to modern period in Portugal, to study broad trends in lifestyle through time in score and within body asymmetries: left and right and between agonist and antagonist muscles (e.g. common extensor and common flexor origin). By using within body asymmetries, the sample size can be maintained rather than divided into age categories, because age should no longer be a factor. This will be tested using the modern identified collection of skeletons. Overall expectations based on previous studies are that: 1) the modern skeletons will have the highest frequencies of changes; 2) that within body asymmetries are independent of age, and 3) right side frequencies will be higher particularly for EC related to wear and tear.